Repeated ex situ Spawning in Two Highly Disease Susceptible Corals in the Family Meandrinidae - O’Neil, Keri L.; Serafin, Rachel M.; Patterson, Joshua T.; Craggs, Jamie R. K. (Frontiers in Marine Science, 2021)
Members of the family Meandrinidae are highly susceptible to stony coral tissue loss disease, resulting in population reductions up to 88% in both Dendrogyra cylindrus and Meandrina meandrites along the Florida Reef Tract. Reductions in abundance on this scale leave these species susceptible to limitations in sexual reproduction and natural recovery without intervention. In response to the ongoing outbreak of the disease across the Caribbean, a variety of genetic rescue projects have been implemented to bring disease susceptible species into ex situ culture and preserve living genetic diversity. In this study, corals being held in a long-term ex situ genetic bank were maintained using artificial lighting and temperature cues programmed to mimic natural cycles in Key Largo, FL. Synchronized broadcast spawning events in both species were documented in aquaria over two annual spawning cycles in 2019 and 2020. Timing of gamete release relative to the perceived date and sunset was highly synchronized with wild observations. Up to 21 unique D. cylindrus genotypes collected from reef locations spanning over 230 km contributed gametes to the larval pool. The majority of these parental colonies are no longer alive in the wild. Repeatable and predictable ex situ spawning events such as these will become an essential tool for managed breeding and assisted fertilization in species suffering from severe population declines. These annual events have the potential to produce thousands of genetically diverse offspring for restoration efforts and offer future hope for the long-term survival of these threatened species.